Variations in the definition and perceived importance of positive resection margins in patients with colorectal cancer - an EYSAC international survey - Smith, Henry; Schlesinger, N. H.; Qvortrup, C.; Chiranth, D.; Lundon, D.; Ben-Yaacov, A.; Caballero, C.; Suppan, I.; Kok, J. Herrera; Holmberg, C. J.; Mohan, H.; Montagna, G.; et al. (European journal of surgical oncology, 2023)
Introduction - Microscopically positive resection margins (R1) are associated with poorer outcomes in patients with colorectal cancer. However, different definitions of R1 margins exist. It is unclear to what extent the definitions used in everyday clinical practice differ within and between nations. This study sought to investigate variations in the definition of R1 margins in colorectal cancer and the importance of margin status in clinical decision-making. - Materials and methods - A 14-point survey was developed by members of The European Society of Surgical Oncology (ESSO) Youngs Surgeons and Alumni Club (EYSAC) Research Academy targeting all members of the multidisciplinary team (MDT) treating patients with colorectal cancer. The survey was distributed on social media, in ESSO's monthly newsletter and via national societies. - Results - In total, 137 responses were received. Most respondents were from Europe (89.7%), with the majority from Denmark (56.9%). Less than 2/3 of respondents defined R1 margins as the presence of viable cancer cells ≤1 mm of the margin. Only 60% reported that subdivisions of R1 margins (primary tumour vs tumour deposit vs metastatic lymph node) are routinely available. More than 20% of respondents reported that pathology reports are not routinely reviewed at MDT meetings. Less than half of respondents considered margin status in decision-making for type and duration of adjuvant chemotherapy in Stage III colon cancer. - Conclusion - The definitions and perceived clinical importance of microscopically positive margins in patients with colorectal cancer appear to vary. Adoption of an international dataset for pathology reporting may help to standardise current practices.
Online verfügbar: 11. September 2023, Artikelversion: 16. September 2023
Gesehen am 08.12.2023